PRINSIP – PRINSIP PENGELOLAAN PEMANFAATAN TANAH WAKAF GUNA PENINGKATKAN KESEJAHTERAAN MASYARAKAT - ., Suhirman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Donated land based on wakaf in Indonesia has agreat potential to help fulfill the needs in the field of religion and socio economy of the society, the donation of lands in general must be managed effectively and efficiently based on the purposes and functions under Islamic Law. Donations of  land in Indonesia have been known and implemented by Muslims since Islam came to Indonesia. The wakaf  donation as one of the Islamic institutions in Indonesia has supported the religious life of Islam in particular and the social life of Indonesian in general. Almost all buildings functioned for the social and religious interests such as worshipping places, educational complex, hospital, bording houses, or public facilities stand on land donated by wakaf .  However, it is also realized that there arestill donated lands that have not been optimally managed. Donated in general and donated land based on wakaf  in particular if managed professionally  can give contributions to the community’s economy in order to develop public welfare. Wakaf  donations actually have agreat potential to be managed and empowered and turned into business purposes in accordance with the economic productivity, not only functioned as a means for worshipping places.
Keywords: wakaf as one of the Islamic institutions